A review of sustainable biodiesel production using biomass derived heterogeneous catalysts - Maroa, Semakula; Inambao, Freddie (Engineering in life sciences, 2021)
The production of biodiesel through chemical production processes of transesterification reaction depends on suitable catalysts to hasten the chemical reactions. Therefore, the initial selection of catalysts is critical although it is also dependent on the quantity of free fatty acids in a given sample of oil. Earlier forms of biodiesel production processes relied on homogeneous catalysts, which have undesirable effects such as toxicity, high flammability, corrosion, by‐products such as soap and glycerol, and high wastewater. Heterogeneous catalysts overcome most of these problems. Recent developments involve novel approaches using biomass and bio‐waste resource derived heterogeneous catalysts. These catalysts are renewable, non‐toxic, reusable, offer high catalytic activity and stability in both acidic and base conditions, and show high tolerance properties to water. This review work critically reviews biomass‐based heterogeneous catalysts, especially those utilized in sustainable production of biofuel and biodiesel. This review examines the sustainability of these catalysts in literature in terms of small‐scale laboratory and industrial applications in large‐scale biodiesel and biofuel production. Furthermore, this work will critically review natural heterogeneous biomass waste and bio‐waste catalysts in relation to upcoming nanotechnologies. Finally, this work will review the gaps identified in the literature for heterogeneous catalysts derived from biomass and other biocatalysts with a view to identifying future prospects for heterogeneous catalysts.